Organic Amendment Influences Soil Quality in Farmers’ Field under Rice-based Cropping Systems in Indo-Gangetic Plains of India - Biswas, Tarik Mitran and Biswapati Mandal, Nirmalendu Basak, Ashim Datta, Sunanda (Journal of the Indian Society of Soil Science, 2016)
Indexing soil quality and identification of key soil indicators are essential for maintaining sustainability of agricultural soils. A minimum data set was developed for soils collected from farmers’ field under long-term rice-potato-sesame (R-P-S) and rice-wheat (R-W) cropping systems with NPK and NPK + organic amendment (FYM) under Alfisols in Indo-Gangetic Plains of India. Soil samples (40 geo-referenced) were collected at 0-0.20 m depth from the fields following the same cropping systems for the last ten years. The samples were analyzed for a large number of physical, chemical and biological attributes. The multivariate statistical analysis showed that out of the 38 attributes, organic C, aggregate ratio, microbial biomass C (Cmic), available zinc and b-glucosidase (b-glu) activity were screened as key indicators of soil quality for soils under R-P-S system; whereas, very labile C, mineralizable C and N (Cmin and Nmin), and b-glu activity were found as key indicators of soil quality for soils under R-W cropping system. The overall results indicated that oxidizable organic C and its labile fractions viz., very labile C, Cmic or Cmin and the C-cycle regulating enzyme viz., b-glu activity are the process based key master indicators for the assessment of soil quality. Application of organic amendment with inorganic fertilizer always maintained higher soil quality index for soils under long-term R-P-S and R-W cropping systems.